1999
DOI: 10.1074/jbc.274.6.3686
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of a Retro-inverso Peptide Analogue Mimicking the Foot-and-Mouth Disease Virus Major Antigenic Site

Abstract: The antigenic activity of a 19-mer peptide corresponding to the major antigenic region of foot-and-mouth disease virus and its retro-enantiomeric analogue was found to be completely abolished when they were tested in a biosensor system in trifluoroethanol. This suggests that the folding pattern, which is ␣-helix in trifluoroethanol (confirmed by CD measurement), does not correspond to the biologically relevant conformation(s) recognized by antibodies. The NMR structures of both peptides were thus determined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 27 publications
3
28
1
Order By: Relevance
“…Both isomer L L -and Retro-inverso peptides presented a typical helical pattern in TFE solution; such pattern can be assigned to an a-helix-like conformation having opposite orientation, similar to other studied cases (Petit et al, 1999). It is important to bear in mind that the parent all-L L 1513 peptide is constituted by L L -amino acids and Retro-inverso peptide by D D -amino acids; however, the latter has N !…”
Section: Stereochemical and Topochemical Analyses Of The Msp-1 42-61 supporting
confidence: 74%
See 2 more Smart Citations
“…Both isomer L L -and Retro-inverso peptides presented a typical helical pattern in TFE solution; such pattern can be assigned to an a-helix-like conformation having opposite orientation, similar to other studied cases (Petit et al, 1999). It is important to bear in mind that the parent all-L L 1513 peptide is constituted by L L -amino acids and Retro-inverso peptide by D D -amino acids; however, the latter has N !…”
Section: Stereochemical and Topochemical Analyses Of The Msp-1 42-61 supporting
confidence: 74%
“…CD and NMR studies were performed with peptides having no additional Cys residues as monomer forms for each molecule. Regarding native peptide sequence, the N-terminus Ala 61 on all-Retro and all-Retro-inverso analogues was carboxamidated and a 2-substituted malonic acid derivative was employed to replace the native C-terminus residue as previously reported (Petit et al, 1999). AllRetro 1513 was synthesised by using L L -amino acids and all-Retro-inverso by employing their corresponding enantiomer D D -residues.…”
Section: Msp-1 42-61 Peptide and Pseudopeptide Chemical And Physical mentioning
confidence: 99%
See 1 more Smart Citation
“…One of them corresponds to the GH loop of VP1 and has high variability and flexibility. A conserved Arg-Gly-Asp (RGD) motif is present in the highly variable GH loop and serves as the integrin-binding site [6,8,118]. So far, the VP1 GH loops in all native viruses are present in a disordered ''up'' conformation when examined using X-ray crystal diffraction, whereas that of the O1BFS strain soaked in dithiothreitol shows a well-ordered ''down'' conformation [1,35,56,83,84,89].…”
Section: Structural Proteinsmentioning
confidence: 99%
“…This is a plausible hypothesis considering that the extended conformation is more likely to be flexible and would provide substantial leeway in optimizing common interactions. However, there are two cases where it has been shown that the ri analog does possess turn-like structures similar to the native peptide (19,20). In one of the cases, the presence of a number of glycine residues (three of nine) could be imparting flexibility to the two versions of the peptide allowing the conformational propensities to overlap (19).…”
Section: Discussionmentioning
confidence: 99%